How wind-based renewable energy contribute to CO2 emissions abatement? Evidence from Quantile-on-Quantile estimation - Ali, S.; Muhammad, Saeed Meo * (Springer, 2024)
Renewable energy initiatives are required to achieve carbon neutrality, which is a primary goal of mitigating climate change. Renewable energy is attaining attention as it is environmentally friendly and more effective than typical forms of energy. For a sustainable environment, the latest green energy techniques like wind energy, are predominantly employed in emerging countries. The present study considered the nonlinear wind energy-CO2 emissions nexus in the top ten wind energy-consumer nations (the USA, China, India, Germany, France, Spain, the UK, Brazil, Canada, and Italy). Most previous studies use panel data tools that provide typical outcomes on the wind energy-CO2 emissions nexus, regardless of the reality that few countries have no proof of such a connection individually. The present research, conversely applies a unique econometric methodology “Quantile-on-Quantile” that can analyze time-series dependence in every nation individually to attain global yet country-specific evidence for the nexus between the variables. We specifically investigate how the wind energy quantiles impact the CO2 emissions quantiles asymmetrically by providing a suitable foundation to apprehend the overall dependent framework. The outcomes reveal that the usage of wind energy is helpful in achieving carbon neutrality at distinct quantiles in selected nations. The degree of the asymmetric association between wind energy-CO2 nexus changes by nation, requiring individual attention and awareness on the governments’ part when forming the policies of wind energy to achieve carbon neutrality.